Non-Isothermal Reduction Behavior and Microstructural Characteristics of MoO3 Powder in Pure Hydrogen Atmosphere - Kwon, Wonyong; Kim, Youngmin; Son, MinJu; Lee, Eui Seon; Oh, Sung-Tag (Archives of Metallurgy and Materials, 2026)
The reduction behavior and microstructure of both raw and ball-milled MoO3 powders have been investigated. The raw powder consisted of coarse plate-shaped particles, whereas the powder ball-milled for 5 h showed agglomerates composed of fine equiaxed particles. XRD analysis of the hydrogen-reduced powders indicated that only the diffraction lines for Mo are observed. In contrast, the milled powder exhibited the main peak of Mo and carbides peak as minor phases. The reduction kinetics of MoO3 powders were evaluated by analyzing the extent of peak shift at various heating rates using thermogravimetric analysis. The activation energies for the raw powder were determined to range from 97.5 to 104.4 kJ/mol, which are approximately consistent with the values reported for the isothermal reduction of MoO3 in a hydrogen atmosphere. For the ball-milled powders, the activation energy was measured to be 148.8–167.1 kJ/mol, which was interpreted to be related to the carbides formed by the reaction of Fe and C impurities with Mo.